Secondary Metabolite of Endophytic Fungi Daldinia eschscholtzii from The Leaves of Syzygium polyanthum - Mia Tirta Sari; Hary Widjajanti; Ferlinahayati; Hermansyah; Rian Oktiansyah; Elfita (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
Salam (Syzygium polyanthum) is a plant that is often used by Indonesian people as traditional medicine. The leaves are consumed to treat various diseases. This study reports the endophytic fungi found from S. polyanthum leaves and its secondary metabolites. Endophytic fungi species were determined through morphological and molecular identification. Potato Dextrose Broth medium was used for the cultivation process and ethyl acetate was used as a solvent for the extraction process. Antioxidant tests was carried out by using the DPPH method. Chromatographic techniques were used for the isolation of secondary metabolite and spectroscopic analysis was carried out to identify their chemical structures. The results of morphological and molecular analysis showed that the sample was Daldinia eschscholtzii. The secondary metabolite obtained from this endophytic fungus was idetified as fonsecinone A with good antioxidant activity. The secondary metabolite have the potential to become a source antioxidants through further research.